Kekuatan Otot Perut, Daya Ledak Otot Lengan, Tinggi Lompatan dan Hasil Pukulan Smash Penuh pada Atlet Bulutangkis - Christie Brenda Gabriella Koloway; Joshua Runtuwene; Fima Lanra Fredrik Gerald Langi (Universitas Sam Ratulangi, 2021)
Background: Badminton is one of the most popular sports in the world, including in Indonesia. Badminton has been around since the 1930s. The strength of the abdominal muscles contributes to a full smash during hitting. Explosive power is an important biometric ability in sports activities, because the explosive power will determine how hard people can hit, kick, jump, run and so on. Jump height is a component of physical fitness to measure leg muscle power. The purpose of this study was to analyze the correlation between abdominal muscle strength, arm muscle explosive power, jump height and the result of a full smash in badminton athletes. Methods: This is a correlational research with cross-sectional approach. This research in the Badminton Field of SMK N 2 Manado in November 2020, using an analytical method with a cross-sectional design. The population is all PB athletes in Manado. The research instrument used was for abdominal muscle strength (sit-ups), for the explosive power of the arm muscles (two hand medicine ball put test), for the height of the jump (vertical jump test), the results of the smash. Data analysis used two stages, namely univariate and bivariate. Results: The results showed that the most distributed respondents based on male sex (62%), the average value of abdominal muscle strength (25.72), the average value of arm muscle explosive power (1.52), the average value – the average jump height (2), and the average value of the smash results (16.44). The results of bivariate analysis showed that there was no relationship between abdominal muscle strength (rcount = 0.211 < rtable= 0.273), arm muscle explosive power (rcount = 0.020) < rtable = 0.273), and jump height (rcount = -0.008 < rtable = 0.273) with a smash hit. Conclusion: That can be conclude there is no correlation between abdominal muscle strength, arm muscle explosive power, and jump height with the results of smash hits.